Érudition et relations de voyages au siècle des Lumières : le cas des voyageurs britanniques à l’Académie de Lorraine (1697-1736) - Jérémy Filet (Viatica)
This article investigates the connections between mobility and scholarship by exploring the cultural exchanges between the Duchy of Lorraine and the British Isles in the first half of the 18th Century. By examining the comparative history of the Duchy of Lorraine and the British Isles, we will show that the educational academy of Duke Leopold was considered a popular stop on the Grand Tour and a centre of Local erudition. The analysis of a selected corpus of travel writing will help us evaluate the influence of travellers from the British Isles on the training of local erudites to uncover cultural transfers between London and Lunéville. Notably, this will reveal one of the earliest examples of the dissemination of Newton’s idea in Continental Europe through the study of a network of scientists imbedded in the republic of letters.